MORPHOLOGICAL CHARACTERISTICS OF PEA (PISUM SATIVUM L.) AND WHEAT (TRITICUM AESTIVUM L.) PLANTS IRRADIATED WITH UV-B - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1996)
ABSTRACT Supplementary UV-B radiation increased the accumulation of UV-B absorbing compounds in pea leaves, but had less effect in wheat. Treated pea leaves showed waviness, bronzing and brown spots. Similar effects were not observed in wheat leaves. A reduction of the total above ground plant heights in both treated species was also evident. In peas, a reduction of plant height was due to a significant decrease in the length of the second internode . . . .